Unvealing a Process for the Establishment of Interoperability Links between Software-Intensive Information Systems - França, Andrey Gonçalves; Frantz, Rafael Zancan; Graciano-Neto, Valdemar Vicente (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Software-Intensive Information Systems (SIIS) often collaborate to accomplish a set of goals. Problem: Due to several factors such as heterogeneity and distribution of these SIIS, interoperability is still a challenge. Currently, despite various available techniques and integration approaches, organizations often adopt ad-hoc methods to create interoperability links between SIISs. This approach frequently results in resource loss and unstable solutions. Solution: We introduce SPPOI, a Structured Process for Pattern-Oriented Integration, designed to bridge the prevalent gap by methodically applying proven integration patterns to overcome the prevalent integration challenges. IS Theory: This research employs General Systems Theory to explore the intricate dynamics within SIIS, highlighting their complex, interdependent structures. Method: We conducted a Grounded Theory (GT) study with industry professionals and a Systematic Literature Review (SLR). The results from both were used to guide the construction of the process. Results: We developed a process for integrating SIIS, addressing key steps and associated challenges. Contributions: An evaluation with specialists was conducted, and the results shows that applying this process can help integration architects foresee potential issues, allocate resources efficiently, and ultimately develop more reliable and effective integration solutions. Furthermore, we anticipate that, in the future, this process could be automated to create interoperability links between SIISs.